Management of pregnancy at and beyond 41 completed weeks of gestation in low-risk women: a secondary analysis of two WHO multi-country surveys on maternal and newborn health - Kyaw Swa Mya; Malinee Laopaiboon; Joshua P. Vogel; Jose Guilherme Cecatti; João Paulo Souza; Ahmet Metin Gulmezoglu; Eduardo Ortiz-Panozo; Suneeta Mittal; Pisake Lumbiganon; on behalf of the WHO multi-country survey on maternal and newborn health research network (BMC, 2017)
Abstract Background The World Health Organization (WHO) recommends induction of labour (IOL) for women who have reached 41 completed weeks of pregnancy without spontaneous onset of labour. Many women with prolonged pregnancy and/or their clinicians elect not to induce, and chose either elective caesarean section (ECS) or expectant management (EM). This study intended to assess pregnancy outcomes of IOL, ECS and EM at and beyond 41 completed weeks. Methods This study is a secondary analysis of the WHO Global Survey (WHOGS) and the WHO Multi-country Survey (WHOMCS) conducted in Africa, Asia, Latin America and the Middle East. There were 33,003 women with low risk singleton pregnancies at ≥41 completed weeks from 292 facilities in 21 countries. Multilevel logistic regression model was used to assess associations of different management groups with each pregnancy outcome accounted for hierarchical survey design. The results were presented by adjusted odds ratios (aORs) with 95% confidence intervals (CIs) after adjusting for age, education, marital status, parity, previous caesarean section (CS), birth weight, and facility capacity index score. Results The prevalence of prolonged pregnancy at facility setting in WHOGS, WHOMCS and combined databases were 7.9%, 7.5% and 7.7% respectively. Regarding to maternal adverse outcomes, EM was significantly associated with decreased risk of CS rate consistently in both databases i.e. (aOR0.76; 95% CI: 0.66-0.87) in WHOGS, (aOR0.67; 95% CI: 0.59-0.76) in WHOMCS and (aOR0.70; 95% CI: 0.64-0.77) in combined database, compared to IOL. Regarding the adverse perinatal outcomes, ECS was significantly associated with increased risks of neonatal intensive care unit admission (aOR1.76; 95% CI: 1.28-2.42) in WHOMCS and (aOR1.51; 95% CI: 1.19-1.92) in combined database compared to IOL but not significant in WHOGS database. Conclusions Compared to IOL, ECS significantly increased risk of NICU admission while EM was significantly associated with decreased risk of CS. ECS should not be recommended for women at 41 completed weeks of pregnancy. However, the choice between IOL and EM should be cautiously considered since the available evidences are still quite limited.